ANALISIS HUBUNGAN PATRON-CLIENT PETANI EKS UPP TCSDP DI DESA KOTO DAMAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Wulandari Wulandari; Evy Maharani; Ermi Tety (Indonesian Journal of Agricultural Economics, 2016)
The patron-client relationship was unbalanced relation between farmers with big compiler, at Koto Damai Village where the big compiler as patron and rubber farmers as client. patron-client relationship make a depedency beetwen each other. This research aim to analyze the patron-client relationship between farmers with big compiler for Ex UPP TCSDP farmers at Koto Damai Village Kampar Kiri Tengah District in Kampar Regency. The research method used survey methode. The sampling method in this research used purposive sampling with criteria of rubber crop age ranging from 21-23 years for 32 rubber farmers. Intake of sample to rubber compiler and factory used snowball sampling method by following its marketing channel. The research result at Koto Damai Village Kampar Kiri Tengah District in Kampar Regency that three marketing channel. Marketing channel 1 start from farmers to big compiler then big compiler sell to rubber factory at Medan. Marketing channel 2 starts from farmers to big compiler with intermediary traders then big compiler sell to rubber factory at Medan. Marketing channel 3 starts from farmers to big compiler with intermediary traders then big compiler sell to rubber factory at Pekanbaru.The relationship farmers with big compiler was patron-client relationship that was any depedent relationship where this relationship was most visible, resiprocity relationship, loyality relationship and personality relationship.